Effects of Nano Fern Extract (Diplazium esculentum) and Humic Acid on Chlorophyll Content of Soybean (Glycine max) - Tita Nopiyanti; Zozy Aneloi Noli; M. Idris (Jurnal Biologi Tropis, 2026)
As the population continues to increase, the demand for soybeans in Indonesia is rising, necessitating effective strategies to enhance soybean growth and production. One such strategy is the use of biostimulants, including nano-fern extract and humic acid. This study aimed to evaluate the effects of different concentrations of nano-fern extract and humic acid, as well as their interaction, on the chlorophyll content and flowering time of soybeans. The experiment was conducted using a Factorial Completely Randomized Design (CRD) with two factors and six replications. Factor A (fern extract) consisted of a control, 100 mg/L of crude fern extract, and nano-fern extract at concentrations of 50, 100, and 150 mg/L. Factor B (humic acid) consisted of a control, 1200 mg/L, and 2500 mg/L. The results showed that the application of nano-fern extract at 150 mg/L and humic acid at 2500 mg/L resulted in higher chlorophyll content than other treatments.